Charting The Path Of Formation: A Phenomenological Exploration Of The Acquired Values Of Former Seminarians - JALANDONI, CEE JAY; CALMA, JUNJIE; SELGAS, JINGGLE; ADORABLE , RENE (Jurnal Studi Agama, 2024)
Seminary formation leaves an enduring impact on seminarians that extends far beyond the confines of the seminary walls. As seminarians journeyed through their formation, they are immersed in diverse values, teachings, and experiences that hone their character and worldview. This study explores the acquired values of the former seminarians during their time in seminary formation, exploring how these values continue to shape and influence their lives beyond the confines of the seminary walls. Employing a transcendental phenomenological approach, the researchers interviewed ten former seminarians who spent three to five years in the seminary. Through data analysis, three prominent themes surfaced on the acquired values: spiritual, moral, and personal competencies. These acquired values were not merely abstract concepts but tangible guiding principles that participants actively integrated into various aspects of human experience, including spiritual and ecclesial life, social interactions, and personal and professional development. By paying careful attention to the lived experiences of former seminarians, seminary programs can be crafted to nurture better the spiritual, moral, and personal development of future generations of clergy.